Pathologic Intimal Thickening Plaque Phenotype: Not as Innocent as Previously Thought. A Serial 3D Intravascular Ultrasound Virtual Histology Study - Kovarnik, Tomas; Chen, Zhi; Wahle, Andreas; Zhang, Ling; Skalicka, Hana; Kral, Ales; Lopez, John J; Horak, Jan; Sonka, Milan; Linhart, Ales (Revista espanola de cardiologia (English ed.), 2017)
INTRODUCTION AND OBJECTIVES: Pathologic intimal thickening (PIT) has been considered a benign plaque phenotype. We report plaque phenotypic changes in a baseline/follow-up intravascular ultrasound-based virtual histology study. METHODS: A total of 61 patients with stable coronary artery disease were analyzed from the HEAVEN trial (89 patients randomized between routine statin therapy vs atorvastatin 80mg and ezetimibe 10mg) with serial intravascular ultrasound imaging of nonculprit vessels. We compared changes in 693 baseline and follow-up 5-mm long segments in a novel risk score, Liverpool Active Plaque Score (LAPS), plaque parameters, and plaque composition. RESULTS: The PIT showed the highest increase of risk score and, with fibrous plaque, also the LAPS. Necrotic core (NC) abutting to the lumen increased in PIT (22 ± 51.7; P = .0001) and in fibrous plaque (17.9 ± 42.6; P = .004) but decreased in thin cap fibroatheroma (TCFA) (⿿15.14 ± 52.2; P = .001). The PIT was the most likely of all nonthin cap fibroatheroma plaque types to transform into TCFA at follow-up (11% of all TCFA found during follow-up and 35.9% of newly-developed TCFA), but showed (together with fibrous plaque) the lowest stability during lipid-lowering therapy (24.7% of PIT remained PIT and 24.5% of fibrous plaque remained fibrous plaque). CONCLUSIONS: Over the 1-year follow-up, PIT was the most dynamic of the plaque phenotypes and was associated with an increase of risk score and LAPS (together with fibrous plaque), NC percentage (together with fibrous plaque) and NC abutting to the lumen, despite a small reduction of plaque volume during lipid-lowering therapy. The PIT was the main source for new TCFA segments.
Keywords: Cholesterol, LDL; Lipid; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; stupeň závažnosti nemoci; anticholesteremika; Disease Progression; Placa ateroesclerótica; ezetimib; Angina estable; Lípidos; progrese nemoci; Time Factors; Atherosclerotic plaque; nemoci koronárních tepen; intervenční ultrasonografie; Drug Therapy, Combination; Follow-up study; Middle Aged; mužské pohlaví; Stable angina; Follow-Up Studies; Ecografía intravascular; Intravascular ultrasound; Atorvastatin; následné studie; aterosklerotický plát; Coronary Artery Disease; kombinovaná farmakoterapie; ženské pohlaví; Anticholesteremic Agents; Coronary Vessels; Humans; Ultrasonography, Interventional; Plaque, Atherosclerotic; zobrazování trojrozměrné; uživatelské rozhraní počítače; časové faktory; lidé středního věku; atorvastatin; Estudio de seguimiento; Imaging, Three-Dimensional; LDL-cholesterol; Ezetimibe; User-Computer Interface; Female; Severity of Illness Index; koronární cévy; lidé; Male